Global trends of research on depression in breast cancer: A bibliometric study based on VOSviewer - Chen, Ling; Ren, Tingting; Tan, Yun; Li, Hong (Frontiers in Psychology, 2022)
Background: Controlling breast cancer-related symptoms can reduce breast cancer depression,promote postoperative recovery,and reduce complications, which is beneficial to the prevention and treatment of breast cancer depression. A growing body of research has linked recovery in breast cancer patients to depression. However, there has been no bibliometric analysis to examine this field systematically. This study aims to visualize the literature to identify hotspots and frontiers in breast cancer and depression research to provide guidance and reference for further research. Methods: The publications related to breast cancer depression were retrieved in the Web of Science database between January 1st, 2002 and March 17th, 2022. VOSviewer was used to identify co-occurrences and collaborations among countries, institutions, and keywords. CiteSpace was used to detect keyword bursts. Results: A total of 7350 articles related to breast cancer depression were identified. During 2002-to 2022, the most productive countries in this field were the USA and the People’s Republic of China. The most productive institutions in this field were the University of California, Los Angeles, and the University of Toronto. The Journal of Psycho-oncology, followed by Supportive Care in Cancer One and the Journal of Clinical Oncology，was the journal with the most publications in breast cancer depression research. Of the top 10 journals, seven were from the US, two were from England,and one was from Germany. Five research hotspots of breast cancer depression were identified by co-word analysis. In the core hotspots, research on post-traumatic growth, spiritual interventions, cognitive behavioral therapy, physical activity, and symptom cluster management of breast cancer depression is relatively mature. Burst detection of keywords on breast cancer depression shows the latest hotspots, such as mental health, cancer survivor mortality, activity. Conclusion: The current study revealed that breast cancer depression studies are growing. Attention should be paid to the latest hotspots, such as mental health, cancer survivor mortality, activity.